A Influência da mulher negra na literatura brasileira contemporânea e a maneira como as escritoras lidam com a intersecção de raça, classe e gênero - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This work is based on the analysis of three works of our Brazilian Literature: Quarto de Despejo, by Carolina Maria de Jesus (2016 [orig. 1992]); Olhos d’Água, by Conceição Evaristo (2015); and Primavera para as Rosas Negras, by Lélia Gonzalez (2018). The research examines how their works express issues of race, class, and gender, serving as a means of resistance and social transformation. Based on a qualitative and descriptive approach, the research is grounded in theories of intersectionality and Black feminism, highlighting the impact of these authors' narratives in the struggle against structural racism and the devaluation of Black women in Brazil. The study shows how these writers use literature not only as a space for denouncing inequalities but also as a way of valuing Afro-Brazilian cultures, orality, and collective memory. Their literary works are marked by peripheral experiences, ancestry, and social critique, promoting important reflections on identity, social exclusion, resistance, and the search for belonging, demonstrating the need to pursue racial and gender equity. Throughout the work, it is observed how these authors deconstruct stereotypes, destabilize discriminatory discourses, and contribute to the formation of a critical and anti-racist consciousness. Thus, this work aims to reaffirm the relevance of Black literature as resistance, a means of combating oppression, and a tool for social transformation.
Keywords: Interseccionalidade; Literatura negra; Feminismo negro; LINGUISTICA, LETRAS E ARTES